2021
DOI: 10.1111/rec.13375
|View full text |Cite
|
Sign up to set email alerts
|

Conserving shellfish reefs—a systematic review reveals the need to broaden research efforts

Abstract: Globally, shellfish reefs have experienced unprecedented declines from historical levels, imperiling the surrounding ecosystems and the services they provide. Shellfish conservation and restoration projects have emerged to combat and reverse this decline but are hindered by a scattered knowledge base and a lack of evidence-based best practice. To address this concern, we conducted a systematic review of English-language peer-reviewed articles studying the impacts of conservation-based actions on reef-building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Coupled with a lack of attachment threads, these features may have made the smaller mussels more vulnerable to dislodgment prior to conspecific attachment (a process that can take many hours; Capelle et al 2019) thus inhibiting the emergence of additional resistance in mussel clumps. Green‐lipped mussels are one of the largest mytilid species currently targeted for restoration (Toone et al 2021). This means that they may be more resistant than smaller species to hydrodynamic dispersal following transfer of adults to the seafloor.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with a lack of attachment threads, these features may have made the smaller mussels more vulnerable to dislodgment prior to conspecific attachment (a process that can take many hours; Capelle et al 2019) thus inhibiting the emergence of additional resistance in mussel clumps. Green‐lipped mussels are one of the largest mytilid species currently targeted for restoration (Toone et al 2021). This means that they may be more resistant than smaller species to hydrodynamic dispersal following transfer of adults to the seafloor.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical regions harbour over four times greater diversity of reef-building oysters than temperate regions with a total of 25 tropical species, six temperate species, and seven eurythermal species (Figure 1). A paucity of literature from tropical regions (Beck et al, 2011;Toone et al, 2021) coupled with ongoing taxonomic ambiguities has likely resulted in some species of reef-building oysters being undocumented or not yet described. For example, Saccostrea cucullata has been used as a catch-all name for what is likely multiple species comprised of at least nine genetically distinct lineages (Lam and Morton, 2006;Guo et al, 2018), while the reef-building species Talonostrea salpinx was only described in 2021 (Al-Kandari et al, 2021).…”
Section: Global Diversity Of Reef-building Oystersmentioning
confidence: 99%
“…Restoration has now expanded to other species including Ostrea lurida on the west coast of the USA and Canada (Pritchard et al, 2015), Ostrea edulis in Europe (Pogoda et al, 2019;Preston et al, 2020), and Ostrea angasi and Saccostrea glomerata in Australia (Alleway et al, 2015;Gillies et al, 2018). More research has been conducted on C. virginica than all other species combined, and there is now a need to broaden research to a wider range of reef-building bivalves to provide ecological evidence to inform restoration beyond the United States (Toone et al, 2021). A review of the benefits of other bivalve species that are targets of shellfish reef restoration demonstrated that they provide similar ecosystem services to those provided by C. virginica (Zu Ermgassen et al (2020), however most of these species reviewed are subtropical and temperate.…”
Section: Introductionmentioning
confidence: 99%
“…Equity considerations may include https://www.ecologyandsociety.org/vol27/iss4/art5/ the distribution of benefits and harms related to engineered solutions (Siders and Keenan 2020), and the involvement, or lack thereof, of local communities in the restoration site identification, as technical experts (not community members) are typically the most involved in siting and planning for nature-based engineering (Kochnower et al 2015). The inclusion of indigenous knowledge and voices in the planning, implementation, and harvest of oysters and other shellfish is particularly ripe for further research (Toone et al 2021).…”
Section: Tier 4: Accommodate Water With Active Risk Reduction Measuresmentioning
confidence: 99%